2014
DOI: 10.7883/yoken.67.288
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Neisseria gonorrhoeae Isolates from Guangzhou, China, during 2002–2011

Abstract: SUMMARY: Antibiotic susceptibility of Neisseria gonorrhoeae in Guangzhou during [2002][2003][2004][2005][2006][2007][2008][2009][2010][2011] showed that resistance to penicillin and ciprofloxacin was high, while ceftriaxone remained effective although there was a trend towards reduced sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Since 1992, China has been part of the WHO Western Pacific Region (WPR) Resistance Surveillance Program; however, for several years, the reported data were only limited to several cities, such as Guangzhou (14), Nanjing (15), and Shanghai (16), and the AMR profiles were basically consistent with the patterns found in other regions of the WPR. To our knowledge, there has been no monitoring the AMR of N. gonorrhoeae in Changsha, a megacity close to Guangzhou, where STD incidence is one of the highest in China.…”
mentioning
confidence: 93%
“…Since 1992, China has been part of the WHO Western Pacific Region (WPR) Resistance Surveillance Program; however, for several years, the reported data were only limited to several cities, such as Guangzhou (14), Nanjing (15), and Shanghai (16), and the AMR profiles were basically consistent with the patterns found in other regions of the WPR. To our knowledge, there has been no monitoring the AMR of N. gonorrhoeae in Changsha, a megacity close to Guangzhou, where STD incidence is one of the highest in China.…”
mentioning
confidence: 93%
“…Studies have shown that changes in the bacteria environment was the main reason for the appearance of drug-resistant strains, and not the uneven distribution of infections across different hospitals or wards [ 10 , 11 ]. In recent years, owing to the broad application of antibiotics in hospital as well as self-medication in communities in China, bacteria drug-resistance has reached very high levels [ 12 ]. This prompted the Chinese Health Ministry to issue guidelines for a better use of antimicrobial drugs in hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Compounding HAI-related issues, antibiotic resistance among pathogens is a serious problem, owing to drug abuse stemming from hospital over-prescription as well as excessive self-medication in Chinese communities [6]. Furthermore, multidrug-resistant (MDR) bacteria have become increasingly prevalent, with notable examples being methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum β-lactamase (ESBL)-positive Escherichia coli [7].…”
Section: Introductionmentioning
confidence: 99%